Essential SQL on SQL Server 2008 - Bagui, Sikha Saha (Jones and Bartlett Publishers, 2011)
This book, written for readers who have little or no previous experience with databases, SQL, or SQL Server, provides a very systematic approach to learning SQL (Structured Query Language) using SQL Server. Each chapter is written in a step-by-step manner and has examples that can be run using SQL Server. Using the sample tables and data provided, the reader of this book will be able to do all the examples to experience hands-on SQL programming in SQL Server. The text also presents a series of exercises at the end of the chapters to help readers gain proficiency with SQL. With this book you will learn: Beginning SQL commands how to retrieve and manipulate data using the simple SELECT statement. How to customize SQL Server 2008 s settings and about SQL Server 2008 s functions. How to create, alter, populate and delete tables. About joins, a common database mechanism for combining tables. Query development, the use of views and other derived structures. Simple set operations. About aggregate functions. How to write subqueries and correlated subqueries. How to create and use indexes and constraints. Transaction processing.